Positive and Negative Selection on Noncoding DNA in Drosophila simulans - Haddrill, Penelope R.; Bachtrog, Doris; Andolfatto, Peter (Molecular biology and evolution, 2008)
There is now a wealth of evidence that some of the most important regions of the genome are found outside those that encode proteins, and noncoding regions of the genome have been shown to be subject to substantial levels of selective constraint, particularly in Drosophila. Recent work has suggested that these regions may also have been subject to the action of positive selection, with large fractions of noncoding divergence having been driven to fixation by adaptive evolution. However, this work has focused on Drosophila melanogaster, which is thought to have experienced a reduction in effective population size (Ne), and thus a reduction in the efficacy of selection, compared with its closest relative Drosophila simulans. Here, we examine patterns of evolution at several classes of noncoding DNA in D. simulans and find that all noncoding DNA is subject to the action of negative selection, indicated by reduced levels of polymorphism and divergence and a skew in the frequency spectrum toward rare variants. We find that the signature of negative selection on noncoding DNA and nonsynonymous sites is obscured to some extent by purifying selection acting on preferred to unpreferred synonymous codon mutations. We investigate the extent to which divergence in noncoding DNA is inferred to be the product of positive selection and to what extent these inferences depend on selection on synonymous sites and demography. Based on patterns of polymorphism and divergence for different classes of synonymous substitution, we find the divergence excess inferred in noncoding DNA and nonsynonymous sites in the D. simulans lineage difficult to reconcile with demographic explanations.